PELANGGARAN KESEHATAN dan KESELAMATAN KERJA (K3) : STUDI KASUS LEDAKAN TUNGKU SMELTER PENGOLAHAN NIKEL PT. INDONESIA TSINGSHAN STAINLESS STELL (ITSS) - Iftinah, Nailah Azka; Azfarul, Andias (Prosiding Pendidikan Teknik Boga Busana, 2025)
This report examines the incident of a work accident that occurred at one of the nickel processing plants owned by PT Indonesia Tsingshan Stainless Steel (ITSS) on December 24, 2023, when a powerful explosion shook the furnace of smelter number 4. The accident left 13 people dead and 46 injured. The study was conducted with the approach of Occupational Safety and health (K3) theory to identify the causes in depth of K3 violations that are at the root of the problems in this heartbreaking incident. Through the analysis of Case Studies, a series of fatal omissions were revealed. Lack of hazard identification and risk assessment, inadequate K3 procedures, minimal K3 training, inappropriate use of personal protective equipment (PPE), and weak K3 supervision become the common thread of identified violations, then provide prevention recommendations. The results showed that the accident was caused by the lack of adequate implementation of the K3 management system in the smelter furnace repair process. The recommendations include improving K3 training, improving work procedures, and strengthening K3 supervision and culture.